2022
DOI: 10.1080/22221751.2022.2026741
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated SARS-CoV-2 breakthrough infection and changes in immune response in a mouse model

Abstract: Older individuals are at higher risk of SARS-CoV-2 infection and severe outcomes, but the underlying mechanisms are incompletely understood. In addition, how age modulates SARS-CoV-2 re-infection and vaccine breakthrough infections remain largely unexplored. Here, we investigated age-associated SARS-CoV-2 pathogenesis, immune responses, and the occurrence of re-infection and vaccine breakthrough infection utilizing a wild-type C57BL/6N mouse model. We demonstrated that interferon and adaptive antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
7
27
0
Order By: Relevance
“…Indeed, vaccinated aged mice elicited lower level of immune responses compared to vaccinated young mice, which were found to be due to a low frequency of IgG- and IFN- γ -secreting cells in vaccinated aged mice [33]. These results were parallel to previous findings that older individuals have lower immune responses to approved COVID-19 vaccine than younger individuals [10, 12, 33, 34]. Specially, lower serum IgG levels of SARS-CoV-2 in elderly peoples were from a lower proportion of peripheral spike-specific memory B cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vaccinated aged mice elicited lower level of immune responses compared to vaccinated young mice, which were found to be due to a low frequency of IgG- and IFN- γ -secreting cells in vaccinated aged mice [33]. These results were parallel to previous findings that older individuals have lower immune responses to approved COVID-19 vaccine than younger individuals [10, 12, 33, 34]. Specially, lower serum IgG levels of SARS-CoV-2 in elderly peoples were from a lower proportion of peripheral spike-specific memory B cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although wild-type C57BL/6 mice model is reported as not being a viable in vivo model for the SARS-CoV-2 infection, many studies have shown that common laboratory mice are susceptible to SARS-CoV-2 infection as well [38,39]. Chen Y and coworkers have recently shown the age-associated SARS-CoV-2 pathogenesis, immune responses, occurrence of re-infection and vaccine breakthrough infection using a wild-type C57BL/6 mouse model [40]. Different SARS-CoV-2 variants of concern are being reported to infect the respiratory tract and induce inflammatory response in wild-type laboratory mice [41].…”
Section: Discussionmentioning
confidence: 99%
“…Though several of these studies examined the effects of infection in C57BL6 mice [7,3,[10][11][12] these were limited to single sex or age cohorts or employed strains of SARS-CoV-2 that were too virulent for elucidating immune mechanisms of recovery by genetic screens. Compared to the few studies in C57BL/6 mice, the most comprehensive early studies with mouse-adapted strains characterized infection in Balb/c mice [7,3,11,13] which do not permit the vast number of genetic screens that are possible with transgenic and gene knockout lines on the C57BL/6 background. Important to our future goals of genetically dissecting key immune pathways for disease recovery of knockout mouse strains on the C57BL/6 background, the immune responses and disease severity observed in Balb/c and C57BL/6 mice are different.…”
Section: Discussionmentioning
confidence: 99%
“…As the pandemic progressed, several groups reported on mouse-adapted strains of SARS-CoV-2 that acutely infected mice and produced disease re ecting what was seen in humans at that time [6-8, 14, 3, 9-13]. Though several of these studies examined the effects of infection in C57BL6 mice [7,3,[10][11][12] these were limited to single sex or age cohorts or employed strains of SARS-CoV-2 that were too virulent for elucidating immune mechanisms of recovery by genetic screens. Compared to the few studies in C57BL/6 mice, the most comprehensive early studies with mouse-adapted strains characterized infection in Balb/c mice [7,3,11,13] which do not permit the vast number of genetic screens that are possible with transgenic and gene knockout lines on the C57BL/6 background.…”
Section: Discussionmentioning
confidence: 99%